Indian household balance sheet: Accounting issues and wealth estimation - Akash Malhotra (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2021)
This paper presents a novel estimate of the Indian household balance sheet (HBS) starting from 1970/71 to 2017/18 and studies the evolution of Indian household finance in an international context. Comparative analysis suggests that the Global Wealth Databook (an annual publication of Credit Suisse Research Institute), has been significantly underestimating both the stock of financial assets and liabilities. By contrast, the Reserve Bank of India, in its recent publication, is marginally overestimating the stock of financial assets and institutional liabilities. An analysis of the net financial position of the Indian household sector reveals that India is presently facing what may be called a five balance sheet challenge - critical HBS leverage ratios have continued to climb even during the recovery period post-2010 (following the global financial and economic crisis). The author recommends close monitoring and more frequent releases of the Indian HBS.
Keywords: D14; E01; E21; G51; O57; 330; household balance sheet; wealth accumulation; household debt; financial sectoral accounts; India